Attitudes towards mental health, mental health research and digital interventions by young adults with type 1 diabetes: A qualitative analysis. (10th January 2018) - Clarke, Janine; Proudfoot, Judy; Vatiliotis, Veronica; Verge, Charles; Holmes‐Walker, Deborah J.; Campbell, Lesley; Wilhelm, Kay; Moravac, Catherine; Indu, Pillaveetil S.; Bridgett, Madeleine
Abstract: Background: Young people with type 1 diabetes are at increased risk of mental disorders. Whereas treatment need is high, difficulty recruiting young people with type 1 diabetes into psychosocial studies complicates development, testing and dissemination of these interventions. Objective: Interviews with young adults with type 1 diabetes were conducted to examine attitudes towards mental health and mental health research, including barriers and motivators to participation in mental health studies and preferred sources of mental health support. The interviews were audio‐taped, transcribed and evaluated via thematic analysis. Setting and participants: Young adults with type 1 diabetes were recruited via social media channels of 3 advocacy organizations. A total of 31 young adults (26 females and 5 males) with an average age of 22 years were interviewed between October 2015 and January 2016. Results: Participants were largely unaware of their increased vulnerability to common mental health problems and knew little about mental health research. Major barriers to participation included perceived stigma and lifestyle issues and low levels of trust in researchers. Opportunities to connect with peers and help others were described as key motivators. Psychological distress was considered normal within the context of diabetes. A need for some level of human contact in receiving psychosocial support was expressed. Discussion and conclusion: Findings provide valuable insights into the complex dynamics of engaging young adults with type 1 diabetes in mental health studies. Interviewees provided practical suggestions to assist investigation and delivery of psychosocial interventions for this vulnerable group.